Carbon sequestration, biomass and soil carbon pool estimation in Oak-dominated forests of Hindu-Kush Range Mountains of Pakistan - Rahman, Ataur; Khan, Nasrullah; Rahman, Inayat Ur; Ali, Kishwar; Brauning, Achim (Universiti Kebangsaan Malaysia, 2023)
The present study aimed to determine the vegetation biomass, soil carbon stocks and carbon sequestration potential of Oak-dominated forests. Thirty forest stands having 10 quadrats of 20×20 were randomly sampled. Out of eighteen tree species, twelve species were associated with Group II followed by Groups I and III, with eight species each. Quercus dilatata was the only Oak species recorded in all three groups having maximum density in Group II (56.14). Quercus semecarpifolia accounted the highest proportion of carbon (235 MgC/ha) in Group II. Quercus baloot, being the dominant species of Group I, is found to accommodate the highest quantities of BMC (335±43 Mg/ha) for all size classes. The highest nitrogen content, total nitrogen and carbon-nitrogen ratio were 0.185%, 8.23 and 59.64, respectively, in Group II. The mean bulk density was 1.519 g/cm3 in Group III. The highest soil organic carbon (SOC) was recorded in Group II (2.69%, 119.82 tons/ha). Because of their large aerial scale and high carbon density, Oak-dominated forests in Group II store most of the carbon. These results suggest that organic carbon is a major source of forest carbon with significant climate change mitigation potential that must be conserved and improved by sustainable forest management.